Analisis Komunikasi Interpersonal Keluarga Batak Dalam Film Ngeri-Ngeri Sedap - Yunita Kurnia; Yanto; Sapta Sari (Jurnal STIA Bengkulu, 2023)
The purpose of this research is to analyze the interpersonal communication of Batak family in Ngeri-Ngeri Sedap movie. The method used is qualitative because it is related to the semiotic approach. The results of this study show that the results of the research analysis show that interpersonal communication in the family is important and seen in interpersonal communication in the film has respect (respect) in the movie Ngeri-Ngeri Sedap, namely listening to each other what others are talking about, empathy (feeling), namely the attitude shown by family members who are feeling what other people feel, especially family members, audible (understood), namely the way the prospective son-in-law is understood by his prospective in-laws, clarity (openness), namely the attitude of openness with family members so as not to cause misunderstanding, and Humble (humble), namely the attitude of the head of the family apologizing with his family members.